Pengembangan Model Berbasis Ordinary Least Square untuk Prediksi Pengaruh Usabilitas Aplikasi iPusnas Terhadap Loyalitas Penggunanya - Syifaun Nafisah; Nazul Effendy (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2023)
iPusnas is a digital library application owned by the National Library of Indonesia that provides free e-book lending services for all Indonesian people. This application requires an evaluation to find out how useful it is for users. In addition, many sources of information can be accessed by the public; further research is needed to determine the loyalty of iPusnas users. This research is a quantitative descriptive study with a regression approach carried out on 384 users. The measurement of usability level uses indicators of Effectiveness, Efficiency, Satisfaction, and Learnability by calculating the percentage. The development of the predictor model uses Ordinary Least Square (OLS) Estimation based on Linear Regression. Based on field data analysis, the usability level of the application is 73.66%, while the level of loyalty to its use is 56.26%. This data shows a correlation coefficient of 0.038; it offers a strong influence and has a linear direction. The OLS-based estimation method produces a predictor model equation of Y = 2.833 + 0.05X with a significance level of 0.000. The coefficient confirms the field findings that the usefulness of the iPusnas application will affect user loyalty in utilizing the application as a source of information.